Mapping the LIS Curriculum - Beheshti, Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The course titles and course descriptions of 44 LIS programs were downloaded from the Internet and stored in several files. More than five hundred keyword were chosen from a large list of words extracted from the files. Approximately 350 terms were identified to represent main topics taught in these programs, and grouped to create 57 major concepts. The intensity of these concepts. . .